Analisis Prosedur Program Penyaluran Modal Usaha Mustahik pada Lazis Jateng Kantor Cabang Temanggung - Farah Tsalasatun Fauziah; Siti Afidatul Khotijah (GLOBAL SCIENTS PUBLISHER, 2026)
Zakat has evolved from consumptive distribution to productive zakat, one of whose programs is economic empowerment through business capital disbursement. This study aims to analyze the procedures of the business capital distribution program at LAZIS Jateng Temanggung Branch. This research employs a qualitative approach using a case study method. Data were collected through direct interviews. The findings indicate that the capital distribution procedure is implemented in sequential stages. The coaching and monitoring program encompasses two dimensions: business development coaching and spiritual guidance. However, the program faces challenges regarding the sustainability rate of mustahik businesses. The recommended solutions to address these challenges include enhancing coaching quality, strengthening mustahik recipients’ awareness of moral responsibility, and improving the assessment process.